Influence Quality Product, Image Brand, and Promotion Regarding The Decision to Purchase Nike Shoes in Jakarta East - Dimas Prasetyo Widiatmoko; Subur Karyatun; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to determine the effect of product quality, brand image and promotion on purchasing decisions for Nike shoes in East Jakarta. The population in this study used a purposive sampling technique where the population was taken 100 people with a significance level of 95% and a standard deviation of 25%. This study uses primary data with data collection methods through questionnaires distributed to 100 respondents. The data analysis technique uses multiple linear regression analysis and uses the Statistical Product and Service Solution (SPSS) version 26.0 program. The results showed that product quality had a positive effect significant effect on purchasing decisions for Nike shoes in East Jakarta. Brand image has a positive and significant effect on purchasing decisions for Nike shoes in East Jakarta. Sales promotion has a positive and significant effect on the decision to purchases Nike shoes in East Jakarta.